Effect of Eight Weeks of Resistance Training on Estrogen Hormone Level and Body Fat Percent in Sedentary Postmenopausal Women - Akbar Azamian Jazi; Mahsa Rastegar Moghadam Mansoori (University of Social Welfare & Rehabilitation Sciences, 2012)
Objectives: The purpose of this research was to study the effect of eight weeks of resistance training on plasma level of estrogen hormone and body fat percent in sedentary postmenopausal women. Methods & Materials: Twenty seven sedentary postmenopausal women were purposefully selected as the subjects of this semi-experimental study (mean age 69.52±7.26 years and mean weight of 64.96±7.81 kg). Furtherly,they were randomly divided into experimental (n=13) and control groups (n=14). Fasting blood samples were collected before and after 8 weeks of resistance training. Resistance training was performed at an intensity corresponding to 60-80% of a one-repetition maximum (2 d/wk for 8 weeks). Differences were analyzed by paired t-test and the between group differences by independent t-test. Results: Comparing differences between the groups indicated that plasma estrogen level significantly increased (P=0.003) and resting heart rate significantly decreased (P=0.010) after eight weeks of resistance training. Body fat percent in experimental group significantly increased in comparing pre and post data (P=0.002). Conclusion: Postmenopausal women may not need to consume estrogen at all or if applied, use lower doses of such hormonal therapeutic approach if they perform resistance training. Increasing this hormone levels may be attributed to increasing the production of such hormone in fat and other peripheral tissues.